2002
DOI: 10.3189/172756402781817824
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of permafrost on Vega Island, Antarctic Peninsula, using satellite images and aerial photography

Abstract: ABSTRACT. The work presented deals with detailed mapping of permafrost in Devil Bay,Vega Island, northeastern Antarctic Peninsula. Mapping of landforms and permafrost features within a periglacial plain was performed using high resolution visible satellite images and aerial photography. Two maps of permafrost were produced: one based on analysis and interpretation of visible satellite imagery and another on low-altitude aerial photography, both yielding similar results. The principles of morphogenesis were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…There have been several studies investigating permafrost on James Ross Island and surrounding islands. Electrical resistivity studies have suggested that the active layer here is approximately 1 m deep (Fukuda et al 1992;Ermolin et al 2002Ermolin et al , 2004. Slightly lower measurements for the active laver (22-93 cm) and important inter-annual variability (2009)(2010) were found by using mechanical vertical probing on a transect from the eastern coast of Brandy Bay, over Johnson Mesa and up to Mendel Station, with variation being controlled partly by altitude, substrate and aspect (Engel et al 2010).…”
Section: Periglacial Assemblagementioning
confidence: 97%
See 2 more Smart Citations
“…There have been several studies investigating permafrost on James Ross Island and surrounding islands. Electrical resistivity studies have suggested that the active layer here is approximately 1 m deep (Fukuda et al 1992;Ermolin et al 2002Ermolin et al , 2004. Slightly lower measurements for the active laver (22-93 cm) and important inter-annual variability (2009)(2010) were found by using mechanical vertical probing on a transect from the eastern coast of Brandy Bay, over Johnson Mesa and up to Mendel Station, with variation being controlled partly by altitude, substrate and aspect (Engel et al 2010).…”
Section: Periglacial Assemblagementioning
confidence: 97%
“…The disintegration of Prince Gustav Ice Shelf in 1995 was associated with rapid recession of tributary glaciers (Glasser et al 2011;Davies et al 2012b). Periglacial landforms are today well developed on James Ross Island and on surrounding islands (Lundqvist et al 1995;Ermolin et al 2002Ermolin et al , 2004Strelin et al 2006;Fukui et al 2008). …”
Section: Geological and Glaciological Historymentioning
confidence: 99%
See 1 more Smart Citation
“…This sedimentological issue is addressed in the present study on the basis of cryofacies, which – much like ichnofacies, pedogenic facies or diagenetic facies – represent the signature of a particular secondary agent superposed on primary sedimentary deposits. The concept of cryofacies used herein differs slightly from its earlier applications (Murton & French, ; Murton, ; Ermolin et al ., ; Stephani et al ., ), with cryofacies defined as diverse suites of ground‐ice texture, fabric and structure – related to the host sediment grain‐size composition, moisture content and the mode of permafrost formation (French & Shur, ; Gilbert et al ., ). Ground ice is an important component of frozen sediments in cold regions, forming a lasting palaeoenvironmental archive and recording the thermal and growth history of permafrost in unconsolidated sediments (Murton, ).…”
Section: Introductionmentioning
confidence: 98%
“…Studies of this topic are of signifi cant value for various environmental modelling tasks dealing with global and regional parameters like permafrost distribution, periglacial landscape dynamics, coastal dynamics, and matter and energy fl uxes. The value of remote sensing in permafrost research has already been demonstrated (Pollard & French 1980;Morrissey et al 1986;Lewkowicz & Duguay 1999;Ermolin et al 2002), but only a few approaches discuss permafrost degradation and related landscapes (Sellmann 1975;Jorgenson et al 2001;Hinkel et al 2003;Grosse et al 2005;Lantuit & Pollard 2005). Despite these previous research efforts and the good quality of available remote sensing data, the quantifi cation of permafrost degradation is still a challenge to be met for the pan-Arctic periglacial regions.…”
mentioning
confidence: 99%